«Чий Крим?» Або яким контентом наповнюються міжнародні бази даних наукових публікацій (презентація) - Тимофєєва, Галина Вікторівна; Опришко, Тетяна Сергіївна; Бульвінська, Оксана Іванівна (Ukrainian State University of Science and Technologies, Dnipro, 2024)
UKR: Міжнародні бази даних наукових публікацій часто є майданчиком для поширення антиукраїнських наративів та пропаганди через науковий контент, що надходить з Росії та окупованих територій. Авторами такого контенту є науково-педагогічні працівники закладів вищої освіти і з самої Росії, і з «народних республік» та Криму, а кількість такого контенту має постійну позитивну динаміку. Більше того, в останні роки також європейські та американські наукові видання, що індексуються в авторитетних базах даних, почали просувати статті авторів з Криму та «республік», спершу визнаючи їх російську афільованість, а згодом – виявляючи нерозбірливість у якості соціально-політичних ідей, що пропонуються редакціям видань.

ENG: International databases of scientific publications often serve as a platform for spreading anti-Ukrainian narratives and propaganda through scientific content coming from Russia and the occupied territories. The authors of such content are academic staff of higher education institutions from Russia itself, as well as from the ‘people's republics’ and Crimea, and the number of such content has been constantly growing. Moreover, in recent years, European and American scientific journals indexed in reputable databases have also begun to promote articles by authors from Crimea and the ‘republics’, first recognising their Russian affiliation, and later showing indiscriminate quality of socio-political ideas offered to the editors of the publications.
"Whose Crimea?" Or what Content International Databases of Scientific Publications are Filled with (presentation)
Г. Тимофєєва: 0000-0001-9224-1116; Т. Опришко: ORCID 0000-0002-9282-0182; О. Бульвінська: ORCID 0000-0002-6764-4340
Keywords: міжнародні бази даних наукових публікацій; науковий контент; національна безпека; наукові журнали; DOAJ; Scopus; Web of Science; Index Copernicus; international databases of scientific publications; scientific content; national security; scientific journals; presentation; SOCIAL SCIENCES; SOCIAL SCIENCES::Other social sciences::Library and information science